2015
DOI: 10.1111/pace.12634
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Atrial Fibrillation Using Zero‐Fluoroscopy Technique: A Randomized Trial

Abstract: RFA using ICE imaging and the CARTO 3 mapping system with contact force measurement is capable of eliminating fluoroscopy in patients undergoing PVI. Exclusion of fluoroscopic imaging does not seem to compromise patient safety and does not affect overall procedure duration, RF application time, or mid-term efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
171
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(187 citation statements)
references
References 29 publications
(42 reference statements)
9
171
1
1
Order By: Relevance
“…Bulava et al [16] demonstrated the feasibility of zero fluoroscopy ablation in 40 patients with paroxysmal AF using ICE imaging and three-dimensional EAM mapping with contact force measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Bulava et al [16] demonstrated the feasibility of zero fluoroscopy ablation in 40 patients with paroxysmal AF using ICE imaging and three-dimensional EAM mapping with contact force measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no comparative standard ablation group in these studies. Bulava et al 17 recently published a randomized trial of atrial fibrillation ablation (pulmonary vein isolation) with and without fluoroscopy in matched populations. They demonstrated equivalent procedural duration and success in both groups, without any serious complications.…”
Section: Discussionmentioning
confidence: 99%
“…Bulava et al [24] introduced transseptal puncture only under intracardiac echocontrol. In combination with EAM, this allows most patients to perform PVI without fluoroscopy [24].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it was possible to perform more complex ablations with a significant reduction or even without using fluoroscopy [4][5][6][7][8][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%